2001
DOI: 10.1074/jbc.m006876200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondria and Caspases in Vitamin D-mediated Apoptosis of MCF-7 Breast Cancer Cells

Abstract: . Our laboratory has shown that 1␣,25(OH) 2 D 3 induces morphological and biochemical markers of apoptosis (chromatin and nuclear matrix condensation, and DNA fragmentation) in breast cancer cells (MCF-7) (4, 5); however, the precise mechanism by which 1␣,25(OH) 2 D 3 and the VDR mediate apoptosis is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
97
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(103 citation statements)
references
References 33 publications
6
97
0
Order By: Relevance
“…In addition, although we have shown in this report that VD3 compounds induced caspase activation and PARP cleavage (Figure 4c), it has been reported that apoptosis induced by VD3 compounds could also be involved in caspase-independent pathway (Mathiasen et al, 1999;Narvaez and Welsh, 2001). Consistent with these reports, it has been shown that apoptotic cell death triggered by downregulation of survivin could also be involved in both caspase-dependent and caspase-independent pathways (Shankar et al, 2001;Li, 2003;Liu et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, although we have shown in this report that VD3 compounds induced caspase activation and PARP cleavage (Figure 4c), it has been reported that apoptosis induced by VD3 compounds could also be involved in caspase-independent pathway (Mathiasen et al, 1999;Narvaez and Welsh, 2001). Consistent with these reports, it has been shown that apoptotic cell death triggered by downregulation of survivin could also be involved in both caspase-dependent and caspase-independent pathways (Shankar et al, 2001;Li, 2003;Liu et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…Although calbindin-D 28k in some models has been shown to confer protection against apoptosis by directly inhibiting caspases, such a mode of action is, however, unlikely in our model system because the death is independent of known caspases (4,16,17,52). Furthermore, MCF-7 cells expressing calbindin-D 28k were as sensitive as the control cells to death receptor-induced caspase-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly some studies have shown that vitamin D3 had a modulatory effects (upregulation of proapoptotic genes or down-regulation of proantiptotic genes) on apoptosis related genes (Narvaez et al, 2001;Pirianov et al, 2001;Kizildağ et al, 2010). In a study, it was mentioned close cooperation between VDR action and p53 tumor suppressor pathway (Patel et al, 2012).…”
Section: Discussionmentioning
confidence: 86%